Spatial Distribution of Soil Properties and Soil Fertility Status in the Paddy Rice Field of Oransbari - Djuuna, Irnanda Aiko Fifi; Hastuti, Irena Tri; Baan, Samen; Bachri, Samsul; Kubangun, Siti Hajar; Musaad, Ishak (JOURNAL OF TROPICAL SOILS, 2025)
Soil properties and soil fertility status of paddy rice fields are considered important factors related to the yield and production of rice; therefore it is essential to understand those properties across the farm.  The objectives of this research is to quantify the soil properties and soil fertility status of paddy-rice soil and their spatial variability in Oransbari. Forty-two composite soil samples (0-30 cm) were taken across paddy rice fields and analyzed for soil chemical properties and fertility status.  Geostatistical analysis and ordinary kriging interpolation methods were used to quantify soil variability and its fertility status across the farm.  The results showed that total soil Nitrogen ranges from 0.11% to 0.17%), organic-C (1.47-6.94%), C/N ratio (11-47), total-P (13-99 mg 100 g-1), available-P (30-227 mg kg-1), total-K (27-54 mg 100 g-1), soil pH (5.83-6.93), base saturation (70-100%), and CEC is 30.51-51.23 me 100 g-1. The spatial variability of all soil characteristics exhibited medium and fit the stable model, except for available Phosphorus and Potassium.  Most rice paddy fields in Oransbari showed high soil fertility status, which indicated that high-yield rice production can be achieved for this region, however, land management factors should be considered for sustainable land use.